Genealogy Thinking and Characteristics of Islamic Theology Abdurrahman Wahid - Muhajirin Muhiddin (Journal of Research and Multidisciplinary, 2020)
This study seeks to explore the genealogy of Islamic theological thought and characteristics Abdurrahman Wahid Abdurrahman Wahid Islamic theological thought. The author uses a qualitative approach in this study. The research data used were sourced from library data. This study uses a content analysis technique (content analysis), which is a method of data analysis carried out systematically and objectively. The results of this study indicate that the life of Abdurrahman Wahid is so complex and full of intellectual wandering in his life, especially at the young age of the most wrestling in the pesantren world that makes Abdurrahman Wahid born as a figure of Islamic thinkers whose thoughts are recognized in Indonesia, even because of his flexible thinking and friendly. So Abdurrahman Wahid, in the end, is also widely known in the Western world. On the other hand, the Islamic model believed by Abdurrahman Wahid is applied in his daily life by accommodating all the interests of the community without discriminating against his background. Abdurrahman Wahid's thoughts, ranging from the ideas of pluralism, the concept of indigenization to neo-modernist patterns of Islamic thought that value pluralism and freedom of belief, need to be emphasized as one of the theological ideas in Indonesia. Thus, the thought of Abdurrahman Wahid's theology is no longer only at the level of God alone, but how the teachings of God incarnate in religious life for the sake of creating mutual tolerance and peace.